Kekuatan Hukum Non Disclosure Agreement Dalam Mencegah Bocornya Confidential Information Perusahaan - Nabila, Syadzwina Hindun (Bacarita Law Journal, 2024)
Non Disclosure Agreement is a confidentiality agreement whose participants are companies with their employees or with other people or other companies where the Non Disclosure Agreement becomes very important because it concerns the confidentiality of information from a company. With this Non Disclosure Agreement, it is anticipated that it will reduce the violation of confidential information of the company. This research uses a normative juridical approach method, with specifications that are descriptive analytical. The data used are secondary data obtained from literature studies.. The results of this study indicate that the Non Disclosure Agreement has legal validity because it provides legal protection to people who release confidential information to other parties. Non Disclosure Agreement is also a guarantee or as evidence to claim its rights if in the future there is a violation of the provisions outlined in the Non Disclosure Agreement.